MODERNISED DESIGN OF A HYDROSTATIC DENSIMETER FOR MEASURING DENSITY OF HIGHLY VISCOUS OILS - D. I. Sagdeev; I. M. Abdulagatov; N. K. Nikulin; v. I. Tyulkin (Вестник Дагестанского государственного технического университета: Технические науки, 2020)
Objectives. The aim of this work is to modernise a VT-KHTI densimeter operated by the method of hydrostatic weighing in order to study the density of highly viscous oils and oil products in the temperature range from 293 K to 473 K at atmospheric pressure.Method. Among the many methods for studying density, the following were used in the course of the study: the constant- and variable-volume piezometer method and the method of hydrostatic weighing.Results. The results of the densimetric study of highly viscous oils obtained from the Republic of Tatarstan in the temperature range from 293 K to 473 K at atmospheric pressure. The following grades are presented: Ashalchinskaya oil (super-viscous, SVO); Kuakbash oil (sulphur), Kichuy oil and Devon oil. Following an analysis and selection of methods for measuring density, a technique for error estimation and densimeter calibration is presented. A calculated expression for the hydrostatic weighing method, derived from the modernised hydrostatic densimeter design for measuring the density of highly viscous oils, is presented.Conclusion. The VT-KHTI densimeter for vacuum working fluids has been modernised and calibrated for research work on measuring the dynamic viscosity coefficient of both Newtonian and non-Newtonian liquids.